Radiographic and surgical guide to locate orthodontics micro-screws. Case report - Oré De La Cruz, Jhames (2006)
The microscrews in orthodontia arise like a necessity for a stable anchorage. They are an alternative that appears as a result of the use of dental implants which are gaining popularity due to his versatility and to its therapeutic effectiveness. In this article we made a revision of Literature and presented displayed a case report where a X Rays and surgical technique in order to locate with greater facility and security the place of positioning of the titanium microscrews.